Present criteria for prophylactic ICD implantation: Insights from the EU-CERT-ICD (Comparative Effectiveness Research to Assess the Use of Primary ProphylacTic Implantable Cardioverter Defibrillators in EUrope) project - Zabel, Markus; Schlögl, Simon; Lubinski, Andrzej; Svendsen, Jesper Hastrup; Bauer, Axel; Arbelo, Elena; Brusich, Sandro; Conen, David; Cygankiewicz, Iwona; Dommasch, Michael; Flevari, Panagiota; Galuszka, Jan; et al. (Journal of electrocardiology, 2019)
BACKGROUND: The clinical effectiveness of primary prevention implantable cardioverter defibrillator (ICD) therapy is under debate. It is urgently needed to better identify patients who benefit from prophylactic ICD therapy. The EUropean Comparative Effectiveness Research to Assess the Use of Primary ProphylacTic Implantable Cardioverter Defibrillators (EU-CERT-ICD) completed in 2019 will assess this issue. SUMMARY: The EU-CERT-ICD is a prospective investigator-initiated non-randomized, controlled, multicenter observational cohort study done in 44 centers across 15 European countries. A total of 2327 patients with heart failure due to ischemic heart disease or dilated cardiomyopathy indicated for primary prophylactic ICD implantation were recruited between 2014 and 2018 (>1500 patients at first ICD implantation, >750 patients non-randomized non-ICD control group). The primary endpoint was all-cause mortality, and first appropriate shock was co-primary endpoint. At baseline, all patients underwent 12‑lead ECG and Holter-ECG analysis using multiple advanced methods for risk stratification as well as documentation of clinical characteristics and laboratory values. The EU-CERT-ICD data will provide much needed information on the survival benefit of preventive ICD therapy and expand on previous prospective risk stratification studies which showed very good applicability of clinical parameters and advanced risk stratifiers in order to define patient subgroups with above or below average ICD benefit. CONCLUSION: The EU-CERT-ICD study will provide new and current data about effectiveness of primary prophylactic ICD implantation. The study also aims for improved risk stratification and patient selection using clinical risk markers in general, and advanced ECG risk markers in particular.
Keywords: lidé; výsledek terapie; Implantable cardioverter defibrillator; Observational Studies as Topic; náhlá srdeční smrt; Risk factors; Mortality; prospektivní studie; defibrilátory implantabilní; Evropa; elektrokardiografie; srovnávací výzkum účinnosti; Comparative Effectiveness Research; Humans; Death, Sudden, Cardiac; Defibrillators, Implantable; pozorovací studie jako téma; Prospective Studies; multicentrické studie jako téma; Electrocardiography; Sudden cardiac death; Treatment Outcome; Europe; Multicenter Studies as Topic